2017
DOI: 10.4067/s0719-38902017005000103
|View full text |Cite
|
Sign up to set email alerts
|

COMBINATION OF ISOLATES OF Pochonia chlamydosporia FOR THE CONTROL OF Meloidogyne javanica IN TOMATO

Abstract: Three different isolates of Pochonia chlamydosporia (Pc-3, Pc-10 and Pc-28) were evaluated in a greenhouse experiment when applied individually and in combinations. A control treatment with no application of isolates of P. chlamydosporia var. chlamydosporia was included, while neither isolates nor nematodes were used in another untreated treatment. One-liter pots were filled with sterilized soil, and each pot was infested with 3 g of rice substrate colonized with the respective isolate plus 3,000 eggs of Meloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In agreement with this, similar reproduction was achieved in tomatoes evaluated 45 days after transplanting to pots, containing soil infested with 3000 eggs (Xavier et al 2017). Despite this reason, the low M. incognita development on the trial #1 did not invalidate or disqualify our data, since most results showed consistence in the other trials, except for P. chlamydosporia, which will be discussed separately.…”
Section: Effect Of Resistance Inducers and Biological Control Agents supporting
confidence: 85%
See 1 more Smart Citation
“…In agreement with this, similar reproduction was achieved in tomatoes evaluated 45 days after transplanting to pots, containing soil infested with 3000 eggs (Xavier et al 2017). Despite this reason, the low M. incognita development on the trial #1 did not invalidate or disqualify our data, since most results showed consistence in the other trials, except for P. chlamydosporia, which will be discussed separately.…”
Section: Effect Of Resistance Inducers and Biological Control Agents supporting
confidence: 85%
“…Furthermore, the inoculated plants presented small young galls and the egg masses were not abundant, as on trial #2. Taking this into account, longer period was necessary to allow properly nematode development .Moreover, regarding the evaluation at 40 DAI, similar reproduction was achieved on tomatoes evaluated 45 days after transplanting to pots, containing soil infested with 3000 eggs (Xavier et al 2017). Despite the reason for the poor development, the nematode reproduction parameters of the trial #1 and #2 will be further discussed below.…”
Section: Effect Of Resistance Inducers and Biological Control Agents mentioning
confidence: 90%
“…Colonization and growth of P. chlamydosporia in soil was documented by several authors (LACR 1991, Bontempo et al, 2014, Xavier et al, 2017 (Plate 2a). Abundant growth was observed when P. chlamydosporia was inoculated in the soil as only hyphal fragments and chlamydospores without any food base than applied as colonized sand bran.…”
Section: Colonization In Soilmentioning
confidence: 83%
“…P. chlamydosporia has high ability to colonize the rhizosphere and the persistence was about 10 weeks on tomato rhizosphere. Single or individual isolate treatment of P. chlamydosporia in soil resulted in improved M. javanica control on tomato (Xavier et al, 2017, Coutinho et al, 2021. The application of fungus before planting in the rhizosphere resulted in 50% of infected eggs, 25% reduction of multiplication and root galling of root knot nematode (Affokpon et al, 2015).…”
Section: Colonization Pattern Rhizospherementioning
confidence: 99%
“…In contrast, the effect of three P. chlamydospora isolates (Pc-3, Pc-10, and Pc-28) for the control of M. javanica on tomato was not promising ( Xavier et al., 2017 ) as none of the isolates were able to reduce gall severity whether applied individually or in combination. However, the number of eggs was decreased in comparison to the control for isolate Pc-10 and the mixtures Pc-10 + Pc-3 and Pc-10 + Pc28 + Pc-3.…”
Section: Biological Controlmentioning
confidence: 98%